Getarkan: An Interactive Game Slide Pull Food Chain to Improve Students’ Learning Outcomes in Elementary School - Ardana, I Nyoman Wahyu Adi; Rati, Ni Wayan (Universitas Pendidikan Ganesha, 2024)
The low interest of students in learning science is caused by several things such as the lack of innovative learning models and methods and the use of less interactive learning media. Fun learning media is needed to improve student learning outcomes. The purpose of this research is to develop a valid, practical, and effective interactive game learning media